2017
DOI: 10.1021/acssuschemeng.7b02384
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemistry Analysis of Reaction Thermodynamics for Hydrogenation and Hydrogenolysis of Aromatic Biomass Model Compounds

Abstract: Designing effective and selective reactions at sustainable or mild conditions is key for the valorization or refinery of lignin biomass using H2 reduction methods. However, it remains unclear what are the feasible mildest conditions for the reductive valorization of lignin, at which transformations can be designed. Here, we aim to exploit this critically important question using quantum chemistry calculations to systematically analyze the thermodynamics of hydrogenation and hydrogenolysis of typical functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“… The resulting product distribution is in line with results from the literature . The noble metals in the presence of a hydrogen atmosphere are highly active for both hydrogenation and deoxygenation reactions . Unlike transition metal-based catalysts, the reaction of noble metal catalysts proceeds via simultaneous demethoxylation and aromatic ring saturation.…”
Section: Results and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“… The resulting product distribution is in line with results from the literature . The noble metals in the presence of a hydrogen atmosphere are highly active for both hydrogenation and deoxygenation reactions . Unlike transition metal-based catalysts, the reaction of noble metal catalysts proceeds via simultaneous demethoxylation and aromatic ring saturation.…”
Section: Results and Discussionsupporting
confidence: 86%
“…Ethylbenzene showed approximately 83% conversion compared to phenolic derivatives, which showed complete ring hydrogenation with 100% conversion. Furthermore, the present NiRu-HT0.2 catalyst selectively hydrogenated aromatic rings in comparison to the phenolic hydroxyl group, which is analogous to some of the recent literature. , …”
Section: Results and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Systematical analysis of the thermodynamics of hydrogenolysis of typical functional groups found in lignin have been applied to identify the mildest operation conditions. As a result, the theoretical foundation for the feasibility of designing novel reactions was provided, which demonstrated that new green catalysts, like transition metal catalysts, will allow lignin hydrogenolysis near ideal mild conditions (room temperature, room pressure, and aqueous solvent) [291]. For further information about the state-of-the-art of selective lignin hydrogenolysis, a very interesting published perspective can be consulted in [292].…”
Section: Reductive Depolymerization (Hydrogenolysis)mentioning
confidence: 99%
“…Cellulose and hemicellulose can be converted into platform compounds such as alcohols, furfural, and furan compounds . These platform compounds can then be further converted into bio-aromatics through a series of reactions, such as deoxygenation, dehydrogenation, and cyclization. , Compared with cellulose and hemicellulose, lignin can be directly converted to bio-aromatics, which is regarded as a promising technology …”
Section: Introductionmentioning
confidence: 99%